SISTEM AKUNTANSI PIUTANG PERUSAHAAN PERDAGANGAN DAN PENYEWAAN PIRANTI GPS TRACKER - Slamet Soesanto; Rosalina Ayudia; Filda Agusta Gusan (Institut Teknologi dan Bisnis Swadharma, 2022)
In general, companies sell products in cash and non-cash. If sales volume increases but is not accompanied by cash payments, there will be potential for trade receivables to increase. There are two methods used to assess and record uncollectible accounts, namely the Direct Write-Off Method and the Allowance Method. P.T “SSS” Technologies is a trading and leasing company for GPS tracking devices. Trade receivables of P.T